Evaluasi Pembelajaran Scientific Approach pada Mata Kuliah Assessment Program Studi Pendidikan Agama Islam - Zainul Arifin; Welly Kuswanto (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2026)
The scientific approach in learning is not only relevant to the field of science, but is also crucial for strengthening systematic, reflective, critical, and evidence-based thinking skills in the Assessment course within the Islamic Religious Education Study Program. This article aims to reconstruct the learning evaluation model of the scientific approach by utilizing the EPSA Model framework developed through research and development. This model is directed at assessing the implementation of learning through three main components, namely preliminary activities, core activities, and closing activities. The foundational research used as a reference employs the Plomp development model, covering the planning, testing, and implementation stages. The evaluation instrument was developed through expert validation, readability testing, limited try-outs, and extensive try-outs. Data analysis was conducted using Aiken's content validity, Exploratory Factor Analysis, Confirmatory Factor Analysis, Cronbach's Alpha reliability, and product feasibility assessment. The development results indicate that the construct of the evaluation model consists of learning readiness, spatial arrangement, apperception, observing, questioning, experimenting, analyzing, communicating, assessment, reflection, and follow-up. The instrument is proven to be valid, reliable, and feasible to use. The contribution of this article lies in the assertion that Assessment learning in Islamic Religious Education can be evaluated more comprehensively through the interconnection of scientific processes, learning assessments, and the improvement of lecture quality. Keywords: learning evaluation; scientific approach; Assessment course; Islamic Religious Education; EPSA Model; construct validity; educational assessment